ChemInform Abstract: Chemoselective Coupling of Sugar Oximes and α‐Ketoacids to Glycosyl Amides and N‐Glycopeptides. Issue 37 (16th September 2014) - Poehner, Claudia; Ullmann, Vera; Hilpert, Ramona; Samain, Eric; Unverzagt, Carlo
Abstract The method can be used for the N‐acylated sugars and oligosaccharides bearing small labels, spacers or peptides in the acyl part.